2018
DOI: 10.4103/ejb.ejb_12_18
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease exacerbations and periodontitis: a possible association

Abstract: Background There is an increasing interest concerning the potential link between both chronic obstructive pulmonary disease (COPD) and chronic periodontitis; therefore the association became the research focus.Objective This study intended to evaluate the potential association between the frequency of COPD exacerbations and chronic periodontitis.Patients and methods A total of 250 male patients with COPD were included in the study and were categorized into two groups according to the frequency of exacerbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…For the primary outcome it appears that higher plaque scores were associated with an increased frequency of COPD exacerbations for the majority of included studies, except for Baldomero et al [28] study. Moreover, the included clinical trials, (Zhou et al 2014 [31] and Kucukcoskun et al 2013 [30]) concluded that periodontal therapy in COPD patients may improve lung function and decrease the frequency of COPD exacerbations. Improving oral health by treating periodontal disease, which in turn improved plaque scores, also showed a similar trend.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the primary outcome it appears that higher plaque scores were associated with an increased frequency of COPD exacerbations for the majority of included studies, except for Baldomero et al [28] study. Moreover, the included clinical trials, (Zhou et al 2014 [31] and Kucukcoskun et al 2013 [30]) concluded that periodontal therapy in COPD patients may improve lung function and decrease the frequency of COPD exacerbations. Improving oral health by treating periodontal disease, which in turn improved plaque scores, also showed a similar trend.…”
Section: Discussionmentioning
confidence: 99%
“…Median exacerbations declined from 3 to 2 in the test group, and increased from 2 to 3 in the control group. Zhou et al [31] concluded that the frequency of COPD exacerbation was signi cantly lower in periodontal therapy group when compared with the control group at 2-year follow-up (p < 0.05). Moreover, (FEV1/FVC) and FEV1 were signi cantly higher in the therapy groups when compared with the control group during the follow-up period (p < 0.05).…”
Section: Periodontal Treatment and Frequency Of Copd Exacerbationsmentioning
confidence: 99%
See 3 more Smart Citations